Mesenchymal Stem Cells for Cryptoglandular Anal Fistula: Current State of Art - Eberspacher, Chiara; Mascagni, Domenico; Ferent, Iulia Catalina; Coletta, Enrico; Palma, Rossella; Panetta, Cristina; Esposito, Anna; Arcieri, Stefano; Pontone, Stefano (Frontiers in Surgery, 2022)
Anal fistula is a common disease that needs surgical treatment to be resolved. Despite a variety of surgical options, the major problem is still to cure complex fistulas without any recurrence in the long-term follow-up but, at the same time, to avoid an impairment of continence. In recent years, one solution has been the application of mesenchymal stem cells derived from adipose tissue, especially in association with other treatments, such as the use of fibrin glue or the previous application of a seton. Their initial use in fistulas associated with Crohn’s disease has shown encouraging results. In this non-systematic review our aim is to analyze the use in cryptoglandular fistulas: the rate of healing is not so high, and the number of studies is limited. Therefore, further randomized controlled trials are needed to establish their efficacy in the case of complex cryptoglandular anal fistulas and their possible complications.